Factors Associated with Returning At-Home Specimen Collection Kits for HIV Testing among Internet-Using Men Who Have Sex with Men. (November 2016) - Ricca, Alexandra V.; Hall, Eric W.; Khosropour, Christine M.; Sullivan, Patrick S.
Background: In the United States, men who have sex with men (MSM) are known to disproportionately have HIV. The authors sought to describe the acceptability of providing at-home dried blood spot specimen collection kits for HIV testing among MSM. Methods: Between August 2010 and December 2010, the authors recruited Internet-using, HIV-negative or -unknown MSM to participate in a 12-month study of behavioral risks. Eligible participants were mailed an at-home HIV test. Results: Of the 896 men who were sent a test kit, 735 (82%) returned the kit. Returning a test kit was significantly associated with race ( P = .002), highest level of education ( P = .012), and annual income ( P = .026). The adjusted odds of black, non-Hispanic men returning a test kit were about half of the odds of white, non-Hispanic men returning a test kit (adjusted odds ratios: 0.49; 95% confidence intervals: 0.31-0.78). Conclusions: Men who have sex with men are willing to provide biological specimens as part of an Internet-based HIV prevention study.